2021
DOI: 10.3390/fermentation7040283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metabolic Regulators and Aeration on Isocitric Acid Synthesis by Yarrowia lipolytica Grown on Ester-Aldehyde Fraction

Abstract: Isocitric acid (ICA) has found wide application in medicine as a promising compound with powerful antioxidant activity to combat oxidative stress. In the known microbiological processes of ICA production by non-conventional yeast Yarrowia lipolytica, the pure carbon sources are commonly used. ICA can be also synthetized by Y. lipolytica from ester-aldehyde fraction (EAF)-waste of the ethanol production process. A highly effective method of ICA production from EAF based on regulation of key enzymes (aconitate h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The concentration of dissolved oxygen (DO) is an important parameter to take in account for the CA production [ 38 ] and generally for the production of organic acids such as isocitric acid [ 15 , 39 ], pyruvic acid [ 40 ] and α-Ketoglutaric Acid [ 41 ]. Ferreira et al [ 42 ] showed that raising the oxygen volumetric mass transfer coefficient (Kla), the conversion of crude glycerol by Y. lipolytica W29 to CA increased of 700%.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of dissolved oxygen (DO) is an important parameter to take in account for the CA production [ 38 ] and generally for the production of organic acids such as isocitric acid [ 15 , 39 ], pyruvic acid [ 40 ] and α-Ketoglutaric Acid [ 41 ]. Ferreira et al [ 42 ] showed that raising the oxygen volumetric mass transfer coefficient (Kla), the conversion of crude glycerol by Y. lipolytica W29 to CA increased of 700%.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, the stirrer rates of 200–1000 rpm and air flow rate within the range of 0.24–2.0 vvm generate the pO 2 values of 30–60% saturation, which favored the synthesis of high-value metabolites in Y. lipolytica [ 26 , 28 , 34 , 35 ]. We observed that a rise in pO 2 value from 5 to 60% saturation enhanced ICA production by 3.3 times in Y. lipolytica grown on ester-aldehyde fraction in small fermenters [ 25 ]. In addition, we found that, in Y. lipolytica cultivated at a pO 2 of 50–55% saturation, the yield of ICA from rapeseed oil (Y p ) and the specific rate of ICA synthesis (q p ) were much higher than the values found in the cultures with oxygen deficiency (5–10% saturation) [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…The literature data describe the processes of ICA production from ethanol [ 11 , 12 ], rapeseed oil [ 13 , 14 , 15 ], sunflower oil [ 16 , 17 , 18 , 19 ], glucose [ 20 ], glycerol [ 20 ], raw glycerol [ 21 , 22 , 23 ], and ethanol industry waste [ 24 , 25 ]. The above articles note that Y. lipolytica has the ability to synthesize ICA and citric acid (CA) simultaneously in a proportion that depends on the strain, carbon source, and composition of the growth medium.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations